ARTIFICIAL INTELLIGENCE DEVELOPMENT AS A BASIS FOR CREATIVE ECONOMIC GROWTH AND RECOVERY OF INDONESIA'S NATIONAL ECONOMY - Sri Kasnelly (Aktualita: Jurnal Penelitian Sosial Keagamaan, 2022)
The times have given birth to many new technologies, one of which is artificial intelligence. Of course, this technology must be utilized and adapted, because otherwise, it will make Indonesia lagging. Plus now the world seems to be controlled by digital, everything will be related to digital, including the economic sector. Indonesia is a developing country with an overall medium-scale economic growth rate. There are still many records for the economic sector, including the creative economy sector. Especially after being faced with the COVID-19 pandemic, the economy has become disrupted and has forced the government to prepare new strategies to recover the national economy (PEN). Links between AI, the creative economy and national economic recovery are analyzed using qualitative methods, that the creative economy using AI accelerates national economic recovery.